How Stable Are Human Aesthetic Preferences Across the Lifespan? - Pugach, Cameron; Leder, Helmut; Graham, Daniel J. (Frontiers in Human Neuroscience, 2017)
How stable are human aesthetic preferences, and how does stability change over the lifespan? Here we investigate the stability of aesthetic taste in a cross-sectional study. We employed a simple rank-order preference task using paintings and photographs of faces and landscapes. In each of the four stimulus classes, we find that aesthetic stability generally follows an inverted U-shaped function, with the greatest degree of stability appearing in early to middle adulthood. We propose that one possible interpretation of this result is that it indicates a role for cognitive control (i.e., the ability to adapt cognition to current situations) in the construction of aesthetic taste, since cognitive control performance follows a generally similar trajectory across the lifespan. However, human aesthetic stability is on the whole rather low: even the most stable age groups show ranking changes of at least 1 rank per item over a two-week span. We discuss possible implications for these findings in terms of existing theories of visual aesthetics and in terms of methodological considerations, though we acknowledge that other interpretations of our results are possible.